2017
DOI: 10.3197/096327117x15002190708137
|View full text |Cite
|
Sign up to set email alerts
|

Representing Non-Human Interests

Abstract: In environmental ethics, the legal and political representation of non-humans is a widespread aspiration. Its supporters see representative institutions that give voice to non-humans' interests as a promising strategy for responding to the illegitimate worldwide exploitation of non-human beings. In this article I engage critically with those who support this form of representation, and address two issues central to any account concerned with the legal and political representation of non-human living beings: w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Absent from the negotiations are the tree itself as well as the multitude of species interacting with and depending on it, from fellow plants and root-associated microbes to lichen, insects, birds, and others. Consequently, this lack of representation in the negotiation leads to outcomes skewed against the trees' interest (and that of its natural stakeholders) (Donoso, 2017), which in turn results in an overall unsuccessful compromise for everyone. The way actors are excluded from negotiations through their labelling as resources in the reductionist sustainability concept thus leads to a failure to represent and protect the complexity and interdependence inherent in natural systems.…”
Section: Why Reductionism Makes Sustainability Unsustainablementioning
confidence: 99%
“…Absent from the negotiations are the tree itself as well as the multitude of species interacting with and depending on it, from fellow plants and root-associated microbes to lichen, insects, birds, and others. Consequently, this lack of representation in the negotiation leads to outcomes skewed against the trees' interest (and that of its natural stakeholders) (Donoso, 2017), which in turn results in an overall unsuccessful compromise for everyone. The way actors are excluded from negotiations through their labelling as resources in the reductionist sustainability concept thus leads to a failure to represent and protect the complexity and interdependence inherent in natural systems.…”
Section: Why Reductionism Makes Sustainability Unsustainablementioning
confidence: 99%
“…To reiterate, biocentrism, or more precisely biocentric individualism, is the position within environmental ethics that has focused on individual living beings as loci of moral considerability (for example Schweitzer 1923, Goodpaster 1978, Agar 1997, Sterba 1998, Kallhoff 2014, Donoso 2017. Different versions of this perspective either implicitly assume a certain understanding of life or explicitly defend what constitutes a living being with an immediate interest in showing that such an entity is morally considerable.…”
Section: Life and Moral Considerabilitymentioning
confidence: 99%
“…The bee problem also highlights that it might become appropriate to distinguish between relevant interests and non-relevant interests in this context. Relevant interests, specifically, can ground moral considerability -in that they refer to an entity's wellbeing -which does not apply to every kind of interest that can be identified and, consequently, non-relevant interests do not refer to the flourishing of the individual itself (Donoso 2017). In the bee example, on the first view, the defence of the hive via the individual's self-sacrifice does not appear to constitute a case of relevant interests in that sense, but it could constitute such an interest if it could be shown that the continuation of this specific bee population is relevant to the individual bee's own internal good.…”
Section: Needs and Interestsmentioning
confidence: 99%
“…Further, it excludes any possible interests outside the definition of the societal collective, not the least future generations, ecosystems, and non‐human beings (Goodin, ). For climate policymaking aiming at decarbonisation, it is highly relevant to consider long‐term interests and also to find ways to represent concerns for ecosystems and non‐humans in policymaking, “as if” their interests were represented in the deliberations (Donoso, ; Eckersley & Gagnon, ). Deliberative methods are favoured by some green political theorists as a way to include diverse interests, including to represent those who cannot participate themselves in the decision‐making process (Baber & Bartlett, ; Jennings, ; Lövbrand & Khan, ).…”
Section: Theoretical Perspectives On Actor Relations In Climate Policmentioning
confidence: 99%